Mulheres migrantes no contexto das fronteiras de gênero e arranjos familiares - Angelin, Paulo Eduardo (2012)
The objective of this research was to understand the trajectories of migrant families and, especially, the life trajectories and social roles assigned and represented in society and specifically in the processes of migration, women migrants and northeastern Paraná, living in a neighborhood of the city of São Carlos, São Paulo, called city Aracy, always considering the origin, the regional culture, socioeconomic status and family arrangements. For the achievement of this study were performed in a first phase, conversations with authors who discuss the theme of migration, whether international or domestic were performed. A dialogue with theorists who portray the issue of gender, male domination and sexual division of labor, as well as authors who address the notion of family arrangements was also made. Finally, we worked with authors who discuss women's participation in migratory flows and the coordination and mobilization of kinship networks. Then, through qualitative research, interviews were conducted with 33 migrant women, using a guide and semi-structured individual interviews, which was built as advanced research and theoretical literature. The research shows that women migrants women in question, according to the socio-cultural and family, play different social roles. Family and living arrangements decisively influence the representation of these social roles. But other factors such as the origin, regional culture, the weather conditions and socioeconomic status, may influence these representations, to the point of women from the same family arrangement, act differently in society in general and in the migration process.